72+x+x=(x+1)(x+1)

Simple and best practice solution for 72+x+x=(x+1)(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 72+x+x=(x+1)(x+1) equation:


Simplifying
72 + x + x = (x + 1)(x + 1)

Combine like terms: x + x = 2x
72 + 2x = (x + 1)(x + 1)

Reorder the terms:
72 + 2x = (1 + x)(x + 1)

Reorder the terms:
72 + 2x = (1 + x)(1 + x)

Multiply (1 + x) * (1 + x)
72 + 2x = (1(1 + x) + x(1 + x))
72 + 2x = ((1 * 1 + x * 1) + x(1 + x))
72 + 2x = ((1 + 1x) + x(1 + x))
72 + 2x = (1 + 1x + (1 * x + x * x))
72 + 2x = (1 + 1x + (1x + x2))

Combine like terms: 1x + 1x = 2x
72 + 2x = (1 + 2x + x2)

Add '-2x' to each side of the equation.
72 + 2x + -2x = 1 + 2x + -2x + x2

Combine like terms: 2x + -2x = 0
72 + 0 = 1 + 2x + -2x + x2
72 = 1 + 2x + -2x + x2

Combine like terms: 2x + -2x = 0
72 = 1 + 0 + x2
72 = 1 + x2

Solving
72 = 1 + x2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x2' to each side of the equation.
72 + -1x2 = 1 + x2 + -1x2

Combine like terms: x2 + -1x2 = 0
72 + -1x2 = 1 + 0
72 + -1x2 = 1

Add '-72' to each side of the equation.
72 + -72 + -1x2 = 1 + -72

Combine like terms: 72 + -72 = 0
0 + -1x2 = 1 + -72
-1x2 = 1 + -72

Combine like terms: 1 + -72 = -71
-1x2 = -71

Divide each side by '-1'.
x2 = 71

Simplifying
x2 = 71

Take the square root of each side:
x = {-8.426149773, 8.426149773}

See similar equations:

| 15(v+1)-3v=3(4v+3)-14 | | h-10=2-h | | 9-M=15 | | 2+7=3x+4 | | x-2.7=5.15 | | 19c-10c=9 | | 18=2+2k | | 5x-38=4x-26 | | 8p-7p=20 | | P-61/9=-17/2 | | 9-25x^2+50x+25= | | 6=2/3×-6 | | 12m=11m | | -3x-2(-2+3x)=13 | | 4(x+7)=9x+8 | | -10+7-7y=-5y+9 | | 2x+8+x+9= | | -8(-3-6x)=6(4+2x)-2x | | 20j-18j=16 | | 4.4=-0.55(n+2) | | 1/4y-y | | 11b-7b=11 | | 40.00+0.10x=25.00+0.25x | | 11x-5+10x=180 | | 16d-(-4)-11d+10=49 | | A-2=(3+A) | | 3x-3+6x-12=180 | | (-3x-7)-(5x+2)= | | 9s-2s=14 | | 4x(x-7)=2x(2x-13)-10 | | 11x+5+10x=180 | | 12(2x-5)=4(6x+1) |

Equations solver categories